Dampak Sosial dan Ekonomi Pandemi Covid-19 Terhadap Pedagang Buah Di Kecamatan Curup Kabupaten Rejang Lebong - Paradila Paradila; Dwita Frisdinawati; Putri Milanda Bainamus (Jurnal Riset Rumpun Ilmu Tanaman, 2024)
The study of the Social and Economic Impact of the Covid-19 Pandemic on Fruit Traders in Curup District, Rejang Lebong Regency, aims to analyze the social impact of the COVID-19 pandemic on fruit traders and analyze the economic impact of the COVID-19 pandemic on fruit traders in Curup District. This research was conducted in February - March 2022 in Curup District, Rejang Lebong Regency, with the consideration that in Curup District is part of the livelihood as a livelihood and includes quite a lot of fruit traders. The analytical method used in this study is the Wilcoxon signed rank test analysis method, using the SPSS Statistics for windows software as a tool. Processed using excel software. The results showed that the impact of changes in social behavior and maintaining cleanliness that occurred to traders in Curup District, it has been tested that the indicator variables before and before the covid-19 pandemic on changes in attitude and maintaining cleanliness experienced a significant decrease from 0.05, meaning that there was a change between before and before the COVID-19 pandemic. The economic impact has been tested on indicators of changes in income before and before the covid-19 pandemic, the value of which is small from 0.05, which means there is a change, the covid-19 pandemic situation has a negative impact on economic traders causing a decrease in the monthly average